The impact of the potential entry of copycats: Entry conditions, consumer welfare, and social welfare - GAO, Sarah Y. (Institutional Knowledge at Singapore Management University, 2016)
This article examines the implications of the potential entry of a copycat who produces and sells a copycat (i.e., imitation) product that competes with the incumbent product. By analyzing a two-period dynamic noncooperative game between these two firms, we identify conditions under which the copycat can gain successful market entry. More importantly, we find that the potential entry of a copycat creates (implicit) pressure for the incumbent to lower its selling price; hence, it improves consumer welfare. Finally, we identify conditions under which the potential entry of a copycat can increase social welfare (i.e., consumer welfare and the profit of both firms).